Risk Factors for Malaria Incidence in Communities Who Have Migrated at Salutambung Health Center, Majene Regency, Indonesia - Fadliati (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2022)
Background: Malaria is transmitted through the bite of a female Anopheles mosquito that contains Plasmodium in it. Malaria is one of the infectious diseases that is still a public health problem in the world, including in Indonesia. This study aims to determine the risk factors for malaria incidence in residents of the Salutambung Health Center area of ​​Majene Regency who has migrated. Method: This research is an analytical observational study using a case-control study design. The population in this study were all pulmonary TB patients who had migrated to Malari endemic areas recorded at the Salutambung Health Center. The sample size was determined based on the Lemeshow formula, as many as 117 people consisting of 39 people for the case group and 78 people for the control group with a case-control ratio of 1:2. sampling technique by means of purposive sampling. The data analysis used was univariate analysis and bivariate analysis with an odds ratio (OR) test. Results: The results showed that the variables that were risk factors for the incidence of malaria (OR> 1) were the length of stay in endemic areas (OR=1.484;95%CI=0.655-3.361), installation of wire gauze (OR=1.274;95%CI=0.478- 3.390), and the use of mosquito nets (OR=1.844;95%CI=0.575-5.918). Conclusion: The conclusion of this study is that the length of stay in endemic areas, installation of wire netting, and the use of mosquito nets are risk factors for the incidence of malaria, so it is hoped that the Salutambung Health Center will conduct socialization to the public to use mosquito nets when sleeping at night and take chemoprophylactic drugs when traveling. to malaria-endemic areas.